COMPARISON OF ROUTINE HEMATOLOGY RESULTS BASED ON LOCAL LABORATORY REFERENCE VALUE AND SYSMEX KX-21 REFERENCE VALUE IN HASAN SADIKIN HOSPITAL BANDUNG - Adrian Suhendra (Journal of Medicine and Health, 2015)
Various factors contribute to the routine hematology values in a healthy-looking person. Variability in analysis methods can also influence the results. However, all of the factors above can be standardized. Those variables have to be considered in determining hematology reference values. The aim of this research is to compare routine hematology results based on local RSHS Clinical Pathology laboratory with Sysmex KX-21 reference values in Medical Check Up (MCU) patients. Another aim is to determine own reference values of RSHS Clinical Pathology Laboratory. The subject of research is MCU patients who came to RSHS Clinical Pathology laboratory, Bandung, for medical check-ups and declared healthy by the internist, and meet the inclusion criteria. The method used is diagnostic test research with cross-sectional descriptive design. The result shows that routine hematology values range that is not too different from reference value range used for KX-21 in Japanese population. Nevertheless, the value range acquired in this research is closer to reference values in Wintrobe reference book. In conclusion, this research shows that routine hematology results of normal population in RSHS are closer to Wintrobe reference values compared to Sysmex KX-21 reference value in Japanese population.Â Â Keywords : reference value range, MCU, Wintrobe, Sysmex KX-21